Time-Dependent Anti-inflammatory Effects of a Lipid Extract from Macrocystis pyrifera on Toll-Like Receptor 2 Signaling in Human THP-1 Monocytes - Kok, Jamie Mei Lin; Dowd, Georgina; Cabral, Jaydee; Wise, Lyn (Planta Medica International Open, 2022)
Seaweeds reportedly contain anti-inflammatory compounds; however, little is known about the therapeutic potential of Macrocystis pyrifera. This study investigated the anti-inflammatory properties of a methanol:chloroform extract, chromatographic fractions, and fatty acids identified from M. pyrifera (Linnaeus) C. Agardh. In human THP-1 monocytes stimulated with the Toll-like receptor 2 agonist lipoteichoic acid, the extract decreased mRNA and protein levels of interleukin-1β, interleukin-8, and monocyte chemoattractant protein-1 to varied degrees at nontoxic concentrations. The greatest anti-inflammatory effects were elicited when the extract was applied between 6 h prior to, and 6 h after, the stimuli. Reduced levels of nuclear factor kappa-light-chain-enhancer of activated B cells signaling proteins were observed in extract-treated cells, with a significant decrease in the myeloid differentiation factor 88 protein abundance relative to stimulated THP-1 cells. Chromatographic fractionation of the extract yielded 40 fractions, of which fraction F25 exhibited the greatest inhibition of monocyte chemoattractant protein-1 production in activated THP-1 cells. Fatty acids abundant within the extract and F25 were identified then tested, individually and in combination, for their anti-inflammatory effects. Myristic acid, palmitoleic acid, and α-linolenic acid, but not the fatty acid combination, inhibited lipoteichoic acid-stimulated monocyte chemoattractant protein-1 production without compromising THP-1 cell viability. These findings indicate that the fatty acid-rich extract and fraction from M. pyrifera provide anti-inflammatory and cytoprotective effects that may be beneficial for use as a therapeutic.
Keywords: Macrocystis pyrifera (Linnaeus) C. Agardh; Phaeophyta; Laminariaceae; fractionation; fatty acid; inflammation; Toll-like receptor; NFκΒ